Pengaruh Kinerja Guru dan Motivasi Belajar Terhadap Prestasi-Siswa di Smk Surya Pertiwi Cililin - Setiawan, Hasan; Ansen, Yopines (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study examines the impact of teacher effectiveness and learning motivation on the academic performance of students at SMK Surya Pertiwi Cililin. Using a quantitative descriptive method with surveys and statistical analysis, the study sampled 78 students from grades X, XI, and XII through Simple Random Sampling. The findings indicate that teacher effectiveness and learning motivation significantly influence student achievement. Partially, teacher effectiveness has a major impact on academic performance, as evidenced by the t-value (3.384) exceeding the t-table value (1.992) and a significance level of 0.001 < 0.05. These results highlight the importance of improving teaching quality and student interest in learning to enhance academic performance. Therefore, strategies that focus on improving teaching methods and student motivation are expected to contribute to better learning outcomes.